RANCANG BANGUN APLIKASI PERPUSTAKAAN PADA MADRASAH ALIYAH TARBIYATUT THOLABAH - Mudianto, Nurmalis; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Madrasah Aliyah (MA) Tarbiyatut Tholabah an equal school to high school. this MA provides library facilities. Visiting hours students are very limited so most members of the library borrow a book at hour break. To be able to borrow books, students should look for a collection to be borrowed on a bookshelf therefore causes the lending collections to be crowded at the end of hour break. Crowded lending at the end of an hour break cause officers overwhelmed serving members of the library and affect the return book. Late return of books disturb other members of the library, because they can’t borrow books that overdue returned. When a member of the library has been fined resulted in many member of the library who decided not to return a book that is not subject to penalties. This causes the loss of the school. Based on this problem, then the application is built on the MA Tarbiyatut Tholabah library to help members of the library order the book at any time. Moreover, it can overcome the problem of delay in collection of checks, collections search, booking a collection that can be accessed from anywhere, and create reports. The results showed that the application of the library can assist members in providing information delay lending collection, information books owned by the library and can reserve books. Moreover, it can help the library to find out information reports.